Evaluating fall risk in community-dwelling older adults through balance assessment with the Nintendo Wii Balance Board - Tapanya, Weerasak; Sangkarit, Noppharath; Poncumhak, Puttipong; Konsanit, Saisunee (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Falls among older adults, affecting one-third of those aged 65 and above, pose a critical global health concern. This study focuses on using the Nintendo Wii Balance Board (NWBB) to measure the centre of pressure (CoP) sway length, aiming to identify and validate fall risk in older individuals.Methods. Utilising a cross-sectional study design, sixty older adult females aged 65 and above (mean age: 71.03 ± 5.58 years) were classified into fall and non-fall groups based on whether they had experienced one or more fall events in the last six months. Comprehensive CoP sway measurements were conducted on the NWBB using various conditions.Results. Results indicated significant differences in CoP sway variables, particularly in conditions with eyes open/closed on a soft surface (EO/SS and EC/SS) in both anteroposterior (AP) and mediolateral (ML) directions (p < 0.001). A strong positive correlation was found between the time to complete five-time sit-to-stand (Tsit to stand) tests and CoP sway length in EC/ SS conditions for AP (r = 0.761, p < 0.001) and ML directions (r = 0.729, p < 0.001). The study identified an optimal cut-off score for AP sway in EC/SS (> 3.89 cm) with 90.0% sensitivity and 80.0% specificity using receiver operating characteristic (ROC) analysis.Conclusions. The NWBB effectively detects variations in CoP sway during quiet standing on a soft surface, proving valuable for identifying older adults at risk of falling. This research enhances fall risk assessment insights, emphasising the NWBB’s practicality as a tool for pinpointing older individuals susceptible to falls.
Keywords: ageing; game console device; risk of fall; balance; a centre of pressure